Less radical fertility-sparing surgery than radical trachelectomy in early cervical cancer. Issue 1 (1st January 2007) - Rob, L.; Charvat, M.; Robova, H.; Pluta, M.; Strnad, P.; Hrehorcak, M.; Skapa, P.
Abstract : The purpose of this pilot study was to determine feasibility and safety of a novel and less radical fertility-preserving surgery; laparoscopic lymphadenectomy with sentinel lymph node identification (SLNI) followed by large cone or simple trachelectomy. Obstetrical and oncologic outcomes were evaluated. Twenty-six patients (6-IA2, 20-IB1) selected on basis of favorable cervical tumor characteristics and the desire to maintain fertility underwent laparoscopic SLNI, frozen section (FS), and a complete pelvic lymphadenectomy as first step of treatment. All of nodes were submitted for microscopic evaluation (sentinel nodes for ultramicrostaging). After a 7-day interval, large cone or simple vaginal trachelectomy was performed in patients with negative nodes. The average of sentinel nodes per side was 1.50 and the average of total nodes was 28.0. Four FS were positive (15.4%). In these cases, Wertheim radical hysterectomy type III was immediately performed. We had no false-negative SLN neither on FS nor on final pathology assessment. Median follow-up was 49 months (18–84). One central recurrence (isthmic part of uterus) was observed 14 months after surgery. This patient was treated with radical chemoradiotherapy, and there was no evidence of the disease 36 months after treatment. Fifteen women planned pregnancy, 11 women became pregnant (15 pregnancies), and 7 women delivered eight children (one in 24 weeks, one in 34 weeks, one in 36 weeks, and five between 37 and 39 weeks). We conclude that lymphatic mapping and SLNI improves safety in this fertility sparing surgery. Large cone or simple trachelectomy combined with laparoscopic pelvic lymphadenectomy can be a feasible method with a high successful pregnancy rate